Paleobiogeography of Eocene Radiolarians in the Southwest Pacific - Pascher, Kristina Michaela (11729297) (2017)
This thesis investigates the effect of climatic and oceanographic changes on the distribution of fossil radiolarian assemblages from the early Eocene to early Oligocene (~56–30 Ma) in the Southwest Pacific. Radiolarian assemblages have been analysed from a series of archived cores collected by the Deep Sea Drilling Project (DSDP) and Ocean Drilling Program (ODP). The selected cores form a latitudinal transect designed to investigate the ecological change associated with the transition from the warm ‘greenhouse’ climate of the Eocene into the cooler Oligocene, when continental-scale glaciation is believed to have intiated in Antarctica. High-latitude sites were sampled on the Campbell Plateau (DSDP Site 277), Tasman Rise (DSDP sites 280 and 281) and the Tasman Sea (DSDP Site 283 and ODP Site 1172), while mid-latitude sites were sampled both to the west of New Zealand (DSDP sites 207, 206, 592) and east of New Zealand (ODP Site 1123). New foraminifer oxygen (δ¹⁸O) and carbon (δ¹³C) stable isotope data from DSDP sites 277, 207 and 592 are presented and provide additional age control and insights in the climatic and oceanographic changes in the Southwest Pacific during the early Eocene to early Oligocene. This thesis contributes a comprehensive taxonomic review of Eocene radiolarian taxa with the intention of standardising nomenclature and to resolve synonymies. 213 out of 259 counting groups have been reviewed and assigned to species or subspecies level and 7 new species are yet to be described. All sites have been correlated to the Southern Hemisphere radiolarian zonation, from the upper Paleocene to upper Oligocene (RP6SH to RP17SH). Alternative datums for the base of RP10SH (LO of Artobotrys auriculaleporis) and the base of RP12SH (LO of Lophocyrtis longiventer) are proposed. The early Eocene climatic optimum (EECO, ~53–49 Ma) can be identified by a negative excursion in foraminiferal δ¹⁸O values at Site 207. The radiolarian assemblages at sites 207 (paleolatitude ~46°S) and 277 (paleolatitude ~55°S) during the EECO are dominated by taxa with low-latitude affinities (Amphicraspedum spp. represents up to 89% of total fauna), but many typical low-latitude genera (e.g. Thyrsocyrtis, Podocyrtis, Phormocyrtis) are absent. Following the EECO, low-latitude taxa decrease at Site 207 and disappear at Site 277. Radiolarians are abundant and very diverse at mid-latitude sites 207 and 206 (paleolatitude ~42°S) during the middle Eocene, and low-latitude taxa are common (up to ~15% of the total fauna at Site 207 and ~10% at Site 206). The middle Eocene climatic optimum (MECO, ~40 Ma), although truncated by poor drilling recovery at Site 277, is identified by a negative shift in foraminiferal δ18O values at this site and is associated by a small increase in radiolarian taxa with low-latitude affinities (up to ~5% of total fauna). Early in the late Eocene (~37 Ma), a positive shift in δ¹⁸O values at Site 277 is correlated with the Priabonian oxygen isotope maximum (PrOM). Within this cooling event, radiolarian abundance, diversity and preservation, as well as diatom abundance, increase abruptly at Site 277. A negative δ¹⁸O excursion above the PrOM is correlated to a late Eocene warming event (~36 Ma) and is referred to as the late Eocene climatic optimum (LECO). The LECO is identified using stable isotopes at sites 277 and 592. Radiolarian abundance and diversity decline within this event at Site 277 although taxa with low-latitude affinities increase (up to ~10% of total fauna). At Site 592, radiolarian-bearing sediments are only present during this event with up to ~6% low-latitude taxa. Apart from the LECO, late Eocene radiolarian assemblages at Site 277 are characterised by abundant high-latitude taxa. High-latitude taxa are also abundant during the late Eocene and Oligocene (~38–27 Ma) at DSDP sites 280, 281, 283, and ODP sites 1172 and 1123 and are associated with very high diatom abundance. Radiolarian assemblages are used for reconstructing the evolution of oceanic fronts. The composition of the assemblages suggests that the oscillation between warm subtropical and cool subtropical conditions can be explained by the varying influence of the warm proto-East Australian Current and cold proto-Ross Gyre. In contrast to temperature reconstructions based on geochemical proxies (TEX₈₆, UK’₃₇ and Mg/Ca), which indicate tropical temperatures throughout most of the Eocene, radiolarians indicate warm subtropical conditions during the EECO. Warm surface water masses may have been transported by the proto-East Australian Current to ~55°S during the EECO. During the middle to late Eocene, cool subtropical conditions prevailed in the Southwest Pacific. Localised occurrences of abundant diatoms indicate upwelling areas close to the Tasman Rise in the middle Eocene. The proliferation of radiolarian assemblages and expansion of high-latitude taxa onto the Campbell Plateau in the latest Eocene is explained by a northward expansion of proto-Ross Gyre. In the early Oligocene (~32 Ma), there is an overall decrease in radiolarian abundance and diversity on the Campbell Plateau (Site 277) and diatoms disappear. Major hiatuses in the region indicate intensified bottom-water currents associated with the establishment of the Antarctic Circumpolar Current. A frontal system similar to present day developed in the early Oligocene, with nutrient-depleted subantarctic waters bathing the southern Campbell Plateau, resulting in a more restricted radiolarian assemblage at Site 277.